Using Computer Simulation for Smart Materials in Buildings in Cairo - Abdel Salam Ahmed Soliman (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In the age of modern technology, the world is witnessing a massive shift towards the use of the Internet of Things and smart materials in a variety of fields. The Internet of Things is a technology that enables different devices and objects to communicate and interact with each other, while smart materials are those that have special capabilities such as sensing and automatic response. At the present time smart materials applications got a widespread in commercial buildings and became an aspect to measure building marketability and functionality like (durability, energy conservation, cost efficiency…. etc.), and with the new projects in Egypt specially the new administrative capital which include a wide range of (administrative, mixed-use, residential…etc.) buildings it became a must to use smart material for its function and to keep up with the new technologies and applications. In this article, we will explore the importance of the Internet of Things and smart materials and their innovative applications in buildings. Through case studies to show the benefits of using smart materials in administrative and mixed-use buildings. an applied study using the simulation in Design Builder v 7.0 using smart glass in administrative buildings.